2007
DOI: 10.1007/s12264-007-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of motilin in the hypothalamus and the effect of central erythromycin on gastric motility in diabetic rats

Abstract: Objective To investigate the expression of motilin-immunoreactive neurons in the hypothalamus and the effect of central administration of erythromycin (EM) on the regulation of gastric motility in diabetic rats. Methods The motilin immunoreactive neurons in the hypothalamus and the hippocampus were detected by immunohistochemistry with rabbit anti-motilin polyclonal antibody. To measure the gastric motility, force transducers were surgically affixed to the gastric serosa. A microinjection syringe was connected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…It is well established that the Arc represents an important receptive structure for hormonal, metabolic and neuronal signals reflecting the energy status. It was suggested that the hypothalamus was a main target of motilin action 4,5 for GI tract motility. Our present study shows for the first time that neurons in Arc are sensitive to GD.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is well established that the Arc represents an important receptive structure for hormonal, metabolic and neuronal signals reflecting the energy status. It was suggested that the hypothalamus was a main target of motilin action 4,5 for GI tract motility. Our present study shows for the first time that neurons in Arc are sensitive to GD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that PVN is an important center in energy balance, which receives neural input from the arcuate nucleus and plays a critical role in food intake and energy integration 15 . Neuroanatomy study reveals that neurons in PVN of hypothalamus can project directly to Arc, 16 and motilin positive neurons were observed in PVN 5 . It is questionable whether motilin‐containing neurons in PVN directly project to Arc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations